THE USE OF WHATSAPP APPLICATION FOR LEARNING ENGLISH ONLINE DURING CORONA VIRUS DISEASE-19 PANDEMIC - Walidaini, Fakhri Anisahril (RETAIN, 2021)
Abstract The purpose of this study was to obtain information about the use of the WhatsApp application for learning English online during the pandemic coronavirus disease-19 (COVID-19). The study used a qualitative method with an inductive approach. The respondents involved were twenty five students from SMP Kartika 4 Surabaya, and 21 respondents were students. To capture all the answers from the respondents, the researcher made statement 1, statement 2, statement 3, statement 4, statement 5, statement 6, statement 7, and statement 8. Interviews were conducted well and structured with questions that had been compiled, linked, and developed with related literature. This study's results are the advantages and disadvantages of each skill in using the WhatsApp application to learn English online during the COVID-19 pandemic. The advantages of learning English online through the WhatsApp application during the coronavirus disease (COVID-19) pandemic were dominated by reading and writing skills. Meanwhile, the lack of learning English online through the WhatsApp application during the coronavirus disease (COVID-19) pandemic was dominated by the ability to hear and speak because it was superior in terms of chat features also text files sent from one another. Keywords: WhatsApp, the use of WhatsApp, learning English online, COVID-19.